Economic growth and CO₂ emissions: Evidence from heterogeneous panel of African countries using bootstrap Granger causality - Delphin Kamanda Espoir; Regret Sunge; Frank Bannor (ZBW - Leibniz Information Centre for Economics, 2021)
The relationship between economic growth and environmental pollution continues to attract undying research interest. While existing studies focused on examining the relationship from growth to pollution or pollution to growth, research on the causal relationship between the two variables is still lacking. This study examined the causal relationship between growth and Co2 emissions across 47 African countries using annual panel data from 1995-2016. Unlike other studies in Africa, the uniqueness of this paper is that we employed the methodology developed by Emirmahmutoğlu and Kose (2011), which considers cross-sectional dependence and slope heterogeneity. The empirical results of the study are as follows: (1) the analysis underpinned a bidirectional causal relationship between growth and Co2 emissions in three countries (Burkina Faso, Mauritania, and the Congo Republic), (2) a unidirectional relationship running from growth to Co2 emissions in seven countries (Niger, Sierra Leone, Angola, Mauritius, Mozambique, Uganda, and Kenya), and (3) a unidirectional relationship running from Co2 emissions to growth in nine countries (Lesotho, Namibia, Tanzania, Egypt, Libya, Chad, Ethiopia, Gabon, and Central African Republic (CAR). The results also suggested the neutrality hypothesis for the rest of the countries that were not part of these three groups. Henceforth, we provided policy implications based on the four groups' results.
Keywords: Q53; Q54; Q56; 330; Economic development; Environmental pollution; Cross sectional dependence; Heterogeneity; Granger Causality; Africa